2016
DOI: 10.1111/dom.12700
|View full text |Cite
|
Sign up to set email alerts
|

Addition of sulphonylurea to metformin does not relevantly change body weight: a prospective observational cohort study (ZODIAC‐39)

Abstract: AimTo investigate changes in body weight trajectories after the addition of individual sulphonylureas (SUs) to metformin in patients with type 2 diabetes.Materials and methodsWe conducted a retrospective observational cohort study, in a primary care setting in the Netherlands. Patients aged ≥18 years with type 2 diabetes who were included in the ZODIAC cohort between 1998 and 2012 and who received metformin monotherapy at inclusion (n = 29 195), and had used metformin as monotherapy for at least 1 year before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
4
0
3
Order By: Relevance
“…On the other hand, insulin, sulfonylurea and thiazolidine are known to induce weight gain [39]. On the contrary, it has been reported that metformin decreased body weight, and inhibited the weight gain by insulin and sulfonylurea [19,40,41]. In fact, 42.9% of the patients were prescribed insulin, sulfonylurea and thiazolidine in non-DPP-4 inhibitor group, but 30% of patients in DPP-4 inhibitor group.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, insulin, sulfonylurea and thiazolidine are known to induce weight gain [39]. On the contrary, it has been reported that metformin decreased body weight, and inhibited the weight gain by insulin and sulfonylurea [19,40,41]. In fact, 42.9% of the patients were prescribed insulin, sulfonylurea and thiazolidine in non-DPP-4 inhibitor group, but 30% of patients in DPP-4 inhibitor group.…”
Section: Discussionmentioning
confidence: 99%
“…Out of the different sulfonylurea/metformin combinations studied, glimepiride/metformin combination resulted in 0.1 kg weight gain, gliclazide/metformin combination resulted in 3.9 kg weight gain, and glibenclamide/metformin combination resulted in 3.3 kg weight gain. [ 27 ] Low-dose glimepiride has also demonstrated effective plasma glucose reduction with no reports of hypoglycemia or weight gain. [ 28 ] Low-dose glimepiride, due to its peripheral insulin sensitizing effect, does not cause downregulation of the insulin receptors and thus may prevent unnecessary hyperinsulinemia and β-cell function failure.…”
Section: Discussionmentioning
confidence: 99%
“…As a direct extension of their mechanism of action, the major adverse effect of SUs is hypoglycemia 46, 47 Weight gain is another important side effect of SUs. Many studies have demonstrated increased weight gain in patients on SUs versus metformin 47 and the UKPDS study demonstrated an increase in weight gain with SUs but even more so with insulin 17 , however not all studies have reported an increase in weight gain 48 .…”
Section: The Effect Of Existing Anti-hyperglycemic Drugs On Cardiovasmentioning
confidence: 99%